External Morphological Study of Chrysops flavipes Meigen 1803, (Diptera: Tabanidae). In Iraq (Journal of the College of Basic Education, 2022)
The work included external morphological study of deer fly Chrysops flavipes Meigen 1803, which belongs to family Tabanidae of order: Diptera.The study involved the most important taxonomic external characters of the: head, thorax, abdomen and their appendages.